Energy Consumption-Youth Unemployment Nexus in Europe: Evidence from Panel Cointegration and Panel Causality Analyses - Bilgili, Faik; Ozturk, Ilhan; Kocak, Emrah; Bulut, Umit (International Journal of Energy Economics and Policy, 2017)
This paper employs a panel data set of 20 European countries and examines the impacts of energy consumption on youth unemployment over the period 1990-2011. We employed panel FMOLS and panel DOLS estimations, panel Granger causality tests based on vector error correction model and panel causality tests of Emirmahmutoglu and Kose (2011) and Dumitreschu and Hurlin (2012). According to the panel FMOLS and DOLS estimators results, there is negative impact of energy consumption on youth unemployment rates. In addition, the causality tests yield unidirectional causality from energy consumption to youth unemployment rates. The outcome of this paper explores the importance of energy policies to decrease youth unemployment rates and, hence, it may suggests policymakers follow relevant policies encouraging energy consumption and new potential energy investments to diminish youth unemployment rates. Keywords: energy consumption; youth unemployment; panel analysis; EU JEL Classifications: C33, E24, Q43